Trends in the development of inclusive education in Ukraine (Educational Dimension, 2020)
The purpose of the article is to identify trends in the development of inclusive education in Ukraine and related challenges. Their understanding and consideration in the formation of educational policy will contribute to a more successful process of its implementation. To achieve this goal, the method of desk research was used. It is established that at present the main trends in the implementation of an inclusive approach in education are the focus on the development of a multi-track model, a significant increase in special and inclusive classes of secondary schools and students who study there, decrease in the number of special educational institutions. Difficulties in implementation of inclusive approach in education are associated with the lack of a common understanding of inclusive education, the imperfection of the regulatory framework, the institutional weakness of the newly established amalgamated territorial communities which are responsible for the introduction of inclusive approach at the local level, the uncoordinated efforts of state and local governments, poor material and technical resources of educational institutions, lack of qualified teachers prepared to work with children in conditions of inclusive education.
Keywords: inclusive education; special educational needs; implementation of inclusive approach